Multi-Drug Resistant Bacteria as Aetiological Factors of Infections in a Tertiary Multidisciplinary Hospital in Poland - Sławomir Poletajew; Katarzyna Pawlik; Anna Bonder-Nowicka; Artur Pakuszewski; Łukasz Nyk; Piotr Kryst (MDPI AG, 2021)
Global and local initiatives were recently undertaken to reduce the burden of antibiotic resistance. The aim of the study was to describe the incidence and the aetiology of bacterial infections among hospitalized patients with special attention paid to the multidrug resistant (MDR) bacteria. This retrospective study was based on prospectively collected data from 150,529 consecutive patients hospitalized in a tertiary multidisciplinary hospital in the years 2017-2019. All consecutive microbiological tests from any biological material performed in the analyzed period were included. Microbiological screening tests (n = 10,677) were excluded. The analysis was focused on aetiological factors of bacterial infections, especially the incidence of MDR bacteria and mechanisms of antibiotic resistance. There were 58,789 microbiological tests performed in the analyzed period. The highest testing rate was noticed for intensive care unit (mean of 3.1 tests per one patient), followed by neonatal intensive care unit (2.7), internal medicine (1.9), pediatrics (1.8), and urology (1.2). Among 58,789 tests, 7690 (13.1%) were positive. MDR bacteria were responsible for 1783 infections (23.2%). The most common antibiotic resistance mechanism reported was ESBL production by Klebsiella spp. or Escherichia coli or Enterobacter spp. isolates (47.3% of all MDR cases). ESBL cases were followed by MRSA (14.7%), VRE (14.2%) and MBL producing Klebsiella spp. (5.6%). Among all infections caused by MDR bacteria, 1175 (65.9%) were diagnosed after 72 h of hospitalization (hospital-acquired infections). Apart from AmpC and ESBL producing Escherichia coli, all MDR bacteria were significantly more common in hospital-acquired infection. MDR bacteria are aetiological factors of a significant portion of infections in hospitalized patients with no remarkable change in the incidence in recent years. Production of ESBL is the most common mechanism of antibiotic resistance and should be regarded as one of the most urgent problems in clinical microbiology.